PRINCIPLES OF ARRANGING OLFACTORY ADJECTIVES IN A CHAIN OF ADJECTIVES (IN THE ENGLISH LANGUAGE) - E. V. Ivanova (Вестник Кемеровского государственного университета, 2013)
The article considers chains of adjectives consisting of several olfactory adjectives and those consisting of an olfactory and another perceptive adjective. As a result of the comparative analysis of various contexts, some rules of arranging those adjectives have been deduced. The author points out that cognitive-pragmatic factors influence the arrangement of adjectives in a sentence.